Home-Based Gait Training Using Rhythmic Auditory Cues in Alzheimer's Disease: Feasibility and Outcomes - Wittwer, Joanne E.; Winbolt, Margaret; Morris, Meg E. (Frontiers in Medicine, 2020)
Background/Purpose: Although gait disorders occur early in the course of Alzheimer’s disease (AD) and increase the risk of falling, methods to improve walking in the home setting are poorly understood. This study aimed to determine the feasibility of a home-based gait training program using rhythmic auditory cues for individuals living with mild to moderately severe AD. Methods: Participants had probable AD with no other major conditions affecting locomotion. The intervention consisted of eight progressively modified 45-minute gait training sessions delivered during home visits over four weeks. Experienced physiotherapists provided the therapy, which incorporated rhythmic music cues, for a range of locomotor tasks and ambulatory activities. On the days when the physiotherapist did not attend, participants independently performed a seated music listening activity. Walking speed, cadence, stride length, double limb support duration and gait variability (coefficient of variation (CV)) were measured using an 8m GAITRite® computerised walkway immediately before and after the physiotherapy intervention. Participant satisfaction was also assessed using a purpose-designed questionnaire. Results: Eleven (median age 77.0 y, median ACE III score 66/100, 3 females and 8 males) community-dwelling adults living with AD participated. Wilcoxon Signed Rank tests revealed statistically significant increases in gait speed following the home-based physiotherapy intervention (baseline = 117.5cm/s, post intervention = 129.9cm/s, z = -2.40, p < .05). Stride length also improved (baseline = 121.8cm, post-intervention = 135.6cm, z = -2.67, p < .05). There was no significant change in gait variability. The program was found to be feasible and safe, with no attrition. Participant satisfaction with the home-based music-cued gait training was high and there were no adverse events. Conclusion: A progressively modified gait training program using rhythmic auditory cues delivered at home was feasible, safe and enjoyable. Music-cued gait training can help to reduce the rate of decline in gait stride length and speed in some individuals living with AD.